STUDI OF FRUIT LEATHER PROCESSING OF MANGGO - Yessy Rosalina; Laili Susanti; Tatik Sulasmi (Jurnal Agroindustri, 2013)
Mango varieties Bengkulu is one of high yielding varieties from Bengkulu Province. The plants grow well and produce fruits almost year-around in all regions in the province of Bengkulu. Mango varieties Bengkulu have very large fruit, thick fruit flesh and slightly sour flavors. It makes Mango varieties Bengkulu is very suitable to be consumed in the form of a processed. Fruit leather is one form of processed fruit. Fruit leather is a thin sheet of fruit in dried form. The results showed that the best processing techniques of fruit leather for mango varieties Bengkulu is the process with addition of sugar by 20% and drying temperature at 60 ?C. The treatment produce fruit leather with the best physical appearance and flavor compared with the other treatments.